LWAH INALIH HAKEN, ARTI KIASAN ATAU SEBENARNYA? - Tjahjono, Baskoro Daru; Widianto (Berkala Arkeologi, 1994)
Lwah inalih haken is a sentence contained in the Ciwagreha inscription, which means the river is moved. The transfer of the river flow is carried out because the place through which the river will pass will be built a sacred building complex (temple). The sacred building referred to in the Ciwagreha inscription is associated with the Rara Jonggrang temple complex in Prambanan. Indeed, the one that best fits the cluster of temples as described in the inscription is Candi Rara Jonggrang. If this is true, it means that the river that has been displaced is the Opak River which is located west of the temple. The problem is whether in reality the Opak River. Have you experienced a river flow change? The title above appears due to the fact that the third page of the Rara Jonggrang Temple complex is not as concentric as the other two pages, but is slightly inclined as if to. avoid streams. So that the question arises whether the river was moved or the third page?